Localized lymphadenopathy with myelodysplastic syndrome associated with tuberculosis - Nakaya, Aya (Hematol Rep, 2019)
We report the case of a man who developed myelodysplastic syndrome (MDS) and refractory cytopenia of unilineage dysplasia, 5 months after aortic valve replacement surgery. He also developed fever of unknown origin. After bone marrow- and other laboratory examinations, he was diagnosed with tuberculosis.